Cost Of Study Reinforced Concrete Structures, Structural Steel And Steel Combination Structure - Concrete (Depo Archives Building Case Study District Jepara) - Decky Rochmanto (International Conference on Coastal and Delta Areas, 2017)
Office buildings in its development always use a reinforced concrete structure. Very few and rarely encountered office buildings using steel structures, whereas steel structures are very easy and fast to use with very simple tool installation tools, so it saves procurement costs and time. For that reason it is necessary to review the material used in the determination of the cheap cost in a design of the building structure, in this study take case study of Depo Archive Building of Jepara Regency with level three (3) floor, the part of structure that is reviewed is column, platform. This study uses design design method and unit price analysis method based on Indonesian National Standard (SNI). The design results calculated with SAP 2000 if it is stated strong, then proceed into the calculation of costs. The results of these cost calculations are compared with six combinations of structures using different materials ie Type I (concrete columns, concrete blocks and concrete plates), Type II (concrete columns, concrete blocks and plates using bonded), Type III (concrete columns, steel and concrete plate), Type IV (concrete columns, steel beams and plate using bonded), Type V (steel columns, steel beams and concrete plates), Type VI (steel columns, steel beams and plate using bonded), where the cost the cheapest is on the Type IV structure at a cost of Rp. 851,922,778.91 and the most expensive cost on Type V structures at a cost of Rp. 1,724,793,719.48. Keywords: material, cost, structure concrete, structure steel, plate floor.